2012
DOI: 10.1186/1741-7015-10-81
|View full text |Cite
|
Sign up to set email alerts
|

The role of barrier membranes for guided bone regeneration and restoration of large bone defects: current experimental and clinical evidence

Abstract: Treatment of large bone defects represents a great challenge in orthopedic and craniomaxillofacial surgery. Although there are several methods for bone reconstruction, they all have specific indications and limitations. The concept of using barrier membranes for restoration of bone defects has been developed in an effort to simplify their treatment by offering a sinlge-staged procedure. Research on this field of bone regeneration is ongoing, with evidence being mainly attained from preclinical studies. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
311
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(328 citation statements)
references
References 135 publications
2
311
0
15
Order By: Relevance
“…In a comprehensive review of barrier membranes, Dimitriou et al concludes that several questions still remain to be answered. The additive use of bone graft and the definition of the ideal membrane are unsolved issues and efficacy, safety, and cost effectiveness of barrier membranes must be established before clinical use can be recommended [14]. We found that the combination of rhBMP-2 and a barrier membrane prevented non-union formation and initiated the production of competent bone.…”
Section: Discussionmentioning
confidence: 84%
“…In a comprehensive review of barrier membranes, Dimitriou et al concludes that several questions still remain to be answered. The additive use of bone graft and the definition of the ideal membrane are unsolved issues and efficacy, safety, and cost effectiveness of barrier membranes must be established before clinical use can be recommended [14]. We found that the combination of rhBMP-2 and a barrier membrane prevented non-union formation and initiated the production of competent bone.…”
Section: Discussionmentioning
confidence: 84%
“…Biodegradable and bioresorbable membranes have been tested for guided bone regeneration efficacy in various animal models, including long bone segmental defects. 20 Given the established efficacy of using membranes for guided bone regeneration, we considered whether a similar approach could be used to limit or restrict BMP-2 activity to a defined volume of interest. Nonsteroidal anti-inflammatory drugs (NSAIDs) can delay or prevent bone formation by inhibiting cyclooxygenase-2 (COX-2).…”
mentioning
confidence: 99%
“…One of the possibilities is guided bone regeneration (GBR) when porous membranes are used as mechanical barriers separating the space around the defect. Thanks to such a separation, during the healing process the bone tissue defect is separated from the soft tissue which has much bigger regenerative potential (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Even though many elements of human body, including bone tissue, are capable of regeneration, this ability does not apply to so-called "critical size defects" (CSD) (1,2). Thus, in the case of critical size defects it is necessary to support natural regenerative mechanisms of the human body.…”
Section: Introductionmentioning
confidence: 99%